COMMUNITY STRUCTURE OF PHYTOPLANKTON AND CHLOROPHYLL-α CONCENTRATION IN THE SUNGAI MESJID VILLAGE DUMAI RIAU PROVINCE - Nugraha, Rafiq Prima; Nurrachmi, Irvina; Siregar, Sofyan Husein (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2021)
The research was conducted in December 2019 at Sungai Mesjid Village Dumai Riau Province. This study aims were to know the condition of water quality, know the structure of the phytoplankton community, know the concentration of chlorophyll-a and know the effect between chlorophyll-a concentration and phytoplankton abundance in waters. The method used in this study was a survey method. The research location is divided into 3 station points namely Bangsal Aceh, Marine Station and Jalan Dermaga. The results showed that the quality of waters classified as oligotrophic waters. Phytoplankton found in this study consisted of 4 classes and 12 species of phytoplankton and the abundance of phytoplankton has a range between 195.57 - 244.33 ind./l. Diversity index (H') ranges from 1.2951 - 2.1705, dominance index (D) ranges from 0.24 to 0.46 and uniformity index (E) ranges from 0.7825 to 0.9551. The chlorophyll-a concentration in waters of Sungai Mesjid Village in Dumai ranged from 0.0025 to 0.0210 mg/L. Phytoplankton abundance and chlorophyll-a concentration has a moderate effect, wherewith increasing chlorophyll-a concentration, phytoplankton abundance will also increase.